DESIGNING A WORK PERMIT REPORTING INFORMATION SYSTEM ON HIBA GROUP - Pramitha Dwi Larasati; Ari Irawan; Ayub Boy Sandi Sipahutar (TEKNOKOM, 2022)
In 1949 the HIBA Group was here to meet the transportation needs of the community. The company's commitment is to provide increased customer satisfaction through professional management and operational team support to the demands of the changing times. HIBA Group offers complete, professional, modern, and integrated transportation services. In addition to providing comprehensive, professional, current, and integrated transportation services, the HIBA Group also provides work comfort to employees, especially for maintenance, construction, and bus bodybuilding. In the construction or maintenance process, each activity must report a work permit or Permit to Work (PTW), whose function is to monitor and analyze the work to be carried out. The analysis is carried out from the workers' health, difficulty, the environment, and work tools (PPE). The reporting process is still manual form or conventional system to slow down the work being done if the work is essential for a tender. The PTW must also be analyzed and reported on the related circumstances so that PTW work tends to be slow. An online-based PTW information system Website design was made to simplify and speed up the PTW reporting to solve this problem. The method used for developing information systems uses the Prototype Model with an object-oriented system approach modeled using the Unified Modeling Language (UML). This research is the design of the PTW information system Website used in the HIBA Group.